2003
DOI: 10.1258/000456303322326416
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum markers of bone turnover during normal pregnancy

Abstract: Background Maternal calcium homeostasis adapts during pregnancy to provide for the needs of the growing fetal skeleton. Wide selections of bone turnover markers are currently available to assess the changes taking place; here, data are presented on two serum-based markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 20 publications
1
19
0
2
Order By: Relevance
“…Elevations in bone resorption markers (NTx, CTx, deoxypyridinoline) have been detected as early as the first trimester of pregnancy, well before fetal Ca accretion reaches its peak in the third trimester (12,13,39) . In contrast, no significant increases in markers of bone formation (P1CP, P1NP and bone-specific ALP) have been reported before the third trimester (12,13,39,50) . Markers of bone resorption and bone formation reach their highest concentration during the last trimester of pregnancy (12,13,39,43,50,62,71,75,104 --109) .…”
Section: Maternal Bone Mineral Mobilisation: Bone Turnover Studiesmentioning
confidence: 90%
See 2 more Smart Citations
“…Elevations in bone resorption markers (NTx, CTx, deoxypyridinoline) have been detected as early as the first trimester of pregnancy, well before fetal Ca accretion reaches its peak in the third trimester (12,13,39) . In contrast, no significant increases in markers of bone formation (P1CP, P1NP and bone-specific ALP) have been reported before the third trimester (12,13,39,50) . Markers of bone resorption and bone formation reach their highest concentration during the last trimester of pregnancy (12,13,39,43,50,62,71,75,104 --109) .…”
Section: Maternal Bone Mineral Mobilisation: Bone Turnover Studiesmentioning
confidence: 90%
“…However, no association between breast-milk Ca concentration and maternal vitamin D status (25OHD) was observed in a study of British and Gambian women (242) , and no differences in breast-milk Ca were observed between US mothers who consumed 50 (238) .…”
Section: Influence On the Mothermentioning
confidence: 94%
See 1 more Smart Citation
“…Additional potential confounders include hemodilution affecting serum measurements (confirmed to affect osteocalcin and CTX, Ref. 461), increased GFR and altered creatinine excretion affecting urinary measurements, possible contributions from placenta and other tissues, increased degradation or clearance by the placenta (confirmed to affect osteocalcin, Ref. 769), and lack of fasted or diurnally timed specimens.…”
Section: Human Datamentioning
confidence: 99%
“…However, there is no evidence that Africans and present higher BMD levels. This population presents risk factors for osteoporosis, such as low calcium intake, high parity and prolonged breastfeeding [48][49][50] . The values summarized in Table 1 are most likely the result of the shorter life expectancy in these countries and coding errors, so that the data on Africa are not reliable.…”
Section: Incidence Of Hip Fracture In Africamentioning
confidence: 99%